1995
DOI: 10.1007/bf00311254
|View full text |Cite
|
Sign up to set email alerts
|

Metastases to the regional lymph nodes, lymph node recurrence, and distant metastases in nonadvanced papillary thyroid carcinoma

Abstract: To investigate the biological characteristics of papillary thyroid carcinoma from the perspectives of lymph node metastasis, lymph node recurrence, and distant metastasis, 746 patients with nonadvanced papillary thyroid carcinoma were retrospectively studied. There were 76 men and 670 women with a mean age of 42.7 years. The rate of lymph node metastasis was significantly higher in young patients (aged less than 30 years). Lymph node recurrence was observed in 80 patients and distant metastasis in 13, being se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 13 publications
4
31
1
3
Order By: Relevance
“…Other research groups have investigated the relationship between lymph node metastasis and patient age. Sugino et al evaluated the cases of 746 patients with "nonadvanced PTC" and reported that lymph node metastasis was more frequently observed in patients < 30 yrs [23]. Ahuja et al showed that lymph node metastases were more frequently positive in patients ≤ 40 yrs [24].…”
Section: Prognostic Significance Of Age In Clinical Ptcmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research groups have investigated the relationship between lymph node metastasis and patient age. Sugino et al evaluated the cases of 746 patients with "nonadvanced PTC" and reported that lymph node metastasis was more frequently observed in patients < 30 yrs [23]. Ahuja et al showed that lymph node metastases were more frequently positive in patients ≤ 40 yrs [24].…”
Section: Prognostic Significance Of Age In Clinical Ptcmentioning
confidence: 99%
“…Sugino et al showed that the rate of lymph node metastasis was high in patients < 30 yrs, and distant recurrence was frequently observed in patients > 50 yrs [23]. Table 4 provides the lymph node and distant recurrence rates of 5,784 patients according to patient age [26].…”
Section: A Dfs Of Patientsmentioning
confidence: 99%
“…As a result, there has been controversy surrounding the need for therapy in these cases and how extensive this should be. 35 With regard to the extent of a thyroidectomy, Hay and cols., 35 33,50 These findings suggests that patients with palpable lymphadenopathy have a high risk of nodal recurEn lo que respecta al microcarcinoma papilar tiroideo, dado el desarrollo de las técnicas de diagnóstico por imagen y el uso de la punción aspiración con aguja fina, en los últimos tiempos ha aumentado el diagnóstico incidental de éstos y, con ello, ha aumentado también la controversia acerca de si precisa tratamiento y cual debe ser la extensión de éste. 35 En cuanto a la extensión de la tiroidectomía, Hay y cols, 35 en un estudio sobre 535 microcarcinomas papilares objetivaron un mayor porcentaje de recidivas locorregionales en aquellos sujetos sometidos a una lobectomía unilateral, respecto a los que se realizó una resección bilateral del tiroides (20 y 5% de recidivas a los 20 años, respectivamente), pero sin objetivar diferencias estadísticamente significativas entre la realización de tiroidectomía subtotal, casi total o total.…”
Section: View Of This and Despite That Papillary Thyroid Carcinoma Haunclassified
“…25,50 Incluso tras este, Wada y cols. 25 objetivaron un 16,7% de recidivas ganglionares, porcentaje similar al encontrado en carcinomas papilares de mayor tamaño.…”
Section: View Of This and Despite That Papillary Thyroid Carcinoma Haunclassified
See 1 more Smart Citation